Combination of tevatron searches for the standard model Higgs Boson in the W+ W- decay mode - Aaltonen, T. (2010)
We combine searches by the CDF and D0 Collaborations for a Higgs boson decaying to W+W-. The data correspond to an integrated total luminosity of 4.8 (CDF) and 5.4 (D0) fb-1 of pp̄ collisions at √s=1.96TeV at the Fermilab Tevatron collider. No excess is observed above background expectation, and resulting limits on Higgs boson production exclude a standard model Higgs boson in the mass range 162-166 GeV at the 95% C.L. © 2010 The American Physical Society.